Parent-Child Well-being Dynamics: A Dyadic Analysis of Parental Characteristics and Child Outcomes in Education and Mental Health - Yildirim-Kurtulus, Hacer; Taskin, Sumeyye; Kurtulus, Emin; Satici, Seydi Ahmet; Deniz, M. Engin (SPRINGER, 2026)
Parent-adolescent dyadic relationships play an important role in the development of adolescents during adolescence. However, we know less about the mechanisms underlying parent-adolescent dyadic relationships. This study presents the results of a study conducted on 528 Turkish participants, 264 parents, and 264 adolescents, using actor-partner interdependence modeling. We measured parental self-efficacy, resilience, academic buoyancy, mental toughness, and psychological well-being in the parent-adolescent relationship. When we look at the actor effects between variables, it is seen that the actor effects between parental self-efficacy, psychological resilience, and psychological well-being for parents and the actor effects between mental toughness, academic buoyancy, and psychological well-being for adolescents are all significant. When the joint effects between the variables are analyzed, it is seen that all joint effects are significant except the joint effect of adolescents' academic resilience on parents' psychological well-being. These findings emphasize the importance of dyadic approaches to parental self-efficacy, psychological resilience, academic buoyancy, mental toughness, and psychological well-being in the parent-adolescent relationship.
Keywords: Parental Self-Efficacy; Psychological Resilience; Mental Toughness; Academic Buoyancy; Psychological Well-Being; SELF-EFFICACY; INDIVIDUAL-DIFFERENCES; CONSTRUCT-VALIDITY; HIGH-RISK; RESILIENCE; TOUGHNESS; BEHAVIOR; MOTHERS; TIME; Social Sciences - Other Topics